Public-Private Partnership for Local Economic Development in the Kintampo Municipality of Ghana - Kor, Jacob Aaworbnang Maabobr; Adjei, Justice Samuel (Advances in Social Sciences Research Journal, 2024)
Local governments are regarded as the primary stakeholders in Local Economic Development (LED) yet, they do not have adequate resources to execute their mandate (Ghana National Policy on PPP, 2011). Public-Private Partnership (PPP) presents a viable option for the delivery of local infrastructure and services for LED. The general objective of the study was to assess the contributions and opportunities of PPPs for LED in the Kintampo Municipal Assembly. A descriptive and exploratory study design was used for the study. According to the findings, the only documented PPP projects identified were public toilets and an enterprise development initiative with REP-BAC. There was another ‘loose’ arrangement of PPP between the KMA and the garages at the ‘magazine’. The PPP initiatives contributed to employment creation and income for the local people and internally generated funds for the KMA. Some identified projects were worth the consideration for investment under PPP e.g. Construction of a Lorry station under B.O.T/ Concession and the Upgrading of Kintampo Waterfalls under Concession. However, the low capacity of local partners to raise funds for investment, bad previous experiences of the KMA, poor service delivery by partners, and weak formalization processes by partners were challenging to PPPs in the Municipality. Despite the challenges, PPPs hold great potential for LED in the KMA. As such it is recommended that the KMA should increase awareness of the local people on PPP as an alternative strategy for funding projects for LED, create the enabling environment, and engage the necessary contractual instruments that commit both partners in all PPPs while maintaining proper documentation.